2003
DOI: 10.1046/j.1471-4159.2003.01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated variable prenatal stress alters pre‐ and postsynaptic gene expression in the rat frontal pole

Abstract: Exposure of pregnant women to stress during a critical period of fetal brain development is an environmental risk factor for developing schizophrenia in the adult offspring. We have applied a repeated variable stress paradigm to pregnant Sprague-Dawley rats during the last week of gestation coinciding with the second trimester in human brain development. Here we report our findings from a microarray analysis of the frontal pole of the prenatally stressed adult offspring and non-stressed adult controls compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 99 publications
(137 reference statements)
6
87
2
3
Order By: Relevance
“…Such effects are likely related to a host of neuroanatomical changes and gene expression differences related to PS exposure. For example, multiple studies reported that PS reduced GR density in the adult hippocampus (Henry et al, 1994, Maccari et al, 1995, altered neurogenesis in the dentate gyrus (Lemaire et al, 2000), reduced hippocampal weight (Szuran et al, 1994, and induced widespread gene expression changes that reflect possible PS-induced alterations in hippocampal synaptic function (Kinnunen et al, 2003). Our findings suggest that certain individuals (LR pups in our hands) may be particularly susceptible to developing these effects.…”
Section: Prenatal Stress Differentially Affects Adrenal Hormone Secrementioning
confidence: 52%
“…Such effects are likely related to a host of neuroanatomical changes and gene expression differences related to PS exposure. For example, multiple studies reported that PS reduced GR density in the adult hippocampus (Henry et al, 1994, Maccari et al, 1995, altered neurogenesis in the dentate gyrus (Lemaire et al, 2000), reduced hippocampal weight (Szuran et al, 1994, and induced widespread gene expression changes that reflect possible PS-induced alterations in hippocampal synaptic function (Kinnunen et al, 2003). Our findings suggest that certain individuals (LR pups in our hands) may be particularly susceptible to developing these effects.…”
Section: Prenatal Stress Differentially Affects Adrenal Hormone Secrementioning
confidence: 52%
“…In addition, a study in rats has shown increased BEGAIN expression in the frontal pole in response to prenatal stress as a paradigm for the etiology of schizophrenia. 55 . BEGAIN is highly associated to the postsynaptic density proteins, and particularly to the postsynaptic density 95 (PSD95) 34,56,57 , having 90% co-localization with PSD95 56 , and a role in sustaining the structure of this scaffolding protein 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to an unpredictable prenatal stress regimen, like neonatal ventral hippocampal lesioning, increases the locomotor response to stimulants and disrupts sensorimotor gating, as well as reducing social drive in the offspring (Sams-Dodd et al, 1997, Lipska and Weinberger, 2000, Le Pen and Moreau, 2002, Rueter et al, 2004. Furthermore, cognitive disturbances (social recognition, novel object recognition) and changes in prefrontal markers of glutamatergic neurotransmission are also present in both of these animal preparations (Le Pen et al, 2000, Lipska et al, 2002, Kinnunen et al, 2003, Koenig, 2005. While some prenatal manipulations in rats, such as immune challenge, viral infection and protein malnutrition also recapitulate sensory gating abnormalities and cognitive disturbances, only unpredictable prenatal stress, hippocampal lesioning and prenatal immune challenge in mice generate social impairments (Borrell et al, 2002, Zuckerman et al, 2003, Palmer et al, 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Using the overarching hypothesis that mid-gestational stress is a risk factor for schizophrenia, we exposed pregnant female rats to an unpredictable variable stress paradigm, which produces rat offspring with molecular signatures, sensorimotor gating deficits and hyperdopaminergia similar to what has been observed in schizophrenic patients (Kinnunen et al, 2003, Koenig et al, 2005. In the present report, we examined the social phenotype of the adult male rats after exposure to an unpredictable prenatal stress paradigm.…”
Section: Introductionmentioning
confidence: 99%